Parents’ Domineering Leadership in “Nanti Kita Cerita Tentang Hari Ini” Movie - Adilla, Annisa; Sunarto, Sunarto (Jurnal Komunikasi Pendidikan, 2022)
This research was entitled “Parents’ Domineering Leadership in “Nanti Kita Cerita Tentang Hari Ini” Movie”. As is known, family conflict discourse had always been one of the debates within the household. Most of family disputes comes from the absence of open communication. Some efforts can be done to minimize conflicts within family scope. After all, family is one of the very first places where people starts to communicate to. This study aims to describe parent’s domineering leadership (father) towards his daughter epicted in “NKCTHI”. The object of the study is “Nanti Kita Cerita Tentang Hari Ini” movie, produced in 2020 by Angga Dwimas Sasongko. The research method uses Roland Barthes’ semiotic analysis through the meaning of lexia and the five existing reading codes. In providing evidences, this research will focus on dialogues and symbols taken from 6 specific scenes. The results indicate that the meaning of lexia occurs in form of restraint, emphasis, blame, and subordination. The study concludes that what is shown in “NKCTHI" is related to the representation of patriarchal society where men are considered more important than women and that women are considered as subordinates who do not have courage to speak up against men’s dominating power. This behavior occurs quite repeatedly in family scope which then creates injustice in gender relations that is often displayed by the media industry. Typically, patriarchal culture always displays perfect body, but the depicted perfect body in the media industry tends to show the superiority of masculine character identity which emphasizes the power of self-defense of parent’s domineering leadership